PENGARUH GAYA KEPEMIMPINAN, KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA UNIT REKAM MEDIK RSUD CIBINONG - Bachtiar Fauzi (JURNAL ILMIAH EDUNOMIKA, 2021)
RSUD Cibinong is a government agency in the field of health services type B shade Bogor Regency, which is responsible for serving the community in the field of health. One of the problems faced by the medical record unit is the low performance of employees allegedly affected by various causal factors, such as leadership style, competence and work discipline. In order to analyze the problem, the method used a double linear regression analysis using SPSS 23 program. This study was conducted in 120 respondents. The purpose of this research is to analyze the influence of leadership style, cooperation and work discipline on the employee's performance and to analyze among the three dependent variables that have the most dominant influence on the employee's performance in the medical record unit of RSUD Cibinong. From regression test results, the dominant factors affecting employee performance in RSUD Cibinong are the leadership style variables, this can be seen from the beta coefficient value of the leadership style variable of 0.515, followed by competence with a beta coefficient of 0.321 and working discipline with a beta coefficient of 0.143 value. The conclusion is that employees' performance is influenced by leadership styles, competencies and work disciplines. Leaders should have a flexible attitude towards their employees, not only choosing people who are only close personally without having competent competence and work discipline. But the leader must embrace all its employees to achieve the objectives of the Organization in the team so that the results do not make the employees feel uncomfortable working with his own leadership and small value for the community who found the service At RSUD Cibinong. Keywords: Competence, leadership Style, work discipline